The reactions of the governments of the Americas to the international crises : an overview of policy measures up to 31 March 2009 (ECLAC [Port of Spain]TT, 2009)
Presents a compilation of most of the measures announced by the countries of the Americas up to 31 March 2009.
Keywords: ECONOMIC POLICY